Considering Broad vs. Narrow Personality Traits of Raters as Predictors of Rating Accuracy in Social Media Judgements of Personality - Visser, Selene (School of Management Studies, 2023)
Previous research has shown that the personality characteristics of raters seem to play a minor role in shaping the accuracy of their personality judgments of other people. However, as prior research studies relied largely on broad (i.e., dimension-level) trait measures to operationalise rater personality, it is unclear if raters' narrow (i.e., facet-level) trait measures may predict their rating accuracy. There are reasons to believe that narrow traits may relate more strongly to accuracy compared to broad traits, due to enhanced conceptual correspondence and improved fidelity (rather than bandwidth) relative to accuracy criteria. The aim of the present study was to determine whether narrow traits of raters predict accuracy, and if so, whether these narrow traits increment prediction of accuracy beyond broad traits. To this end, a secondary research design was used. Primary data from a previous study of 456 students' personality judgments of five target social media profiles were reanalysed. Personality traits of judges were operationalised at both broad vs. narrow traits and accuracy criteria were regressed against these predictors. In line with prior research on broad personality traits, the findings revealed that specific narrow traits were not generally predictive of personality rating accuracy from Facebook social media information. However, compared to broad traits, narrow traits were marginally better predictors of accuracy. Overall, results support the growing consensus that rater personality traits are not important to produce accurate ratings of personality, irrespective of the level at which we measure them (broad vs. narrow traits). The study adds to the growing momentum of research indicating raters can be accurate regardless of their personality traits. Therefore, organisations that wish to enhance their rating screening and training programmes might find more value in focusing on rater cognitive factors, rather than on their personality traits.